General. (25th March 2015) - Unknown
Abstract : Twelves Voices from Greece and Rome by Christopher Pelling and Maria Wyke sounds like a title specially commissioned by this very journal, though, alas, we can claim none of the credit! The collaboration arose out of a BBC Radio 3 series on classical literature in collaboration with the Open University and should have a broad appeal. Of the twelve voices six are Greek, six Latin: for the poets, Homer, Sappho, Virgil, Horace; for the tragedians, Euripides; for the historians Herodotus, Thucydides, Caesar, Tacitus; with Cicero for the orators (and philosophers…) and Juvenal for the satirists, paired with the final 'voice' in the collection: Lucian (a striking sign of the growing interest and marketability of Second Sophistic and Imperial Greek authors). This is a stimulating and enjoyable read, which carries one swiftly along. It is not a didactic regurgitation of literary and cultural history (though the final section on 'Translations and Further Reading' gives all the references one needs for further research) but a celebration of the continuing relevance of the Classics:The texts of the ancient world can still speak, not just to us, but with us, and in a range of exhilarating and disturbing ways. They still matter, and what they talk about can still be fresh (whether empire, masculinity, nature, urbanity, madness, rationality, religious commitment and disbelief, family and friendship, desire, or death). (x)